(untitled) (LACCEI, 2024)
Its objective is to determine the relationship between stress and academic procrastination in students of the first cycle of the psychology career of a Private University Arequipa 2022. It is of a quantitative approach, of descriptive, correlational scope, and of a cross-sectional non-experimental design, its sample It is 150 students of the first cycle of the psychology career, to whom two Likert scale questionnaires were applied for each variable, both have reliability and validity. Finding as results that 82.7% of students have medium levels of stress. Regarding academic procrastination, 70.2% present high levels of academic procrastination and 47.1% present high levels in the self-regulation factor. Obtaining a weak positive correlation 0.364.